Behaviour of soft soil improved by floating soil-cement columns - Rashid, Sr. (ICE Publishing, 2018)
Deep mixing method is a soil modification technique, in which the soil is mixed in situ with cement stabiliser agents. Limited attempts have been made to investigate the failure behaviour of soil-cement columns constructed in a floating manner. Hence, this paper aims to examine the failure mechanisms and bearing capacity of floating soil- cement columns, in which columns of 24 mm diameter and 100 mm length were constructed by means of the replacing method below a rigid foundation of 100 mm width in a soft clay bed. Improvement area ratios of 17, 26 and 35 have been explored for parametric investigation. The close range photogrammetry and particle image velocimetry techniques were used to evaluate the associated failure mechanisms. The obtained bearing capacity and failure mechanisms were then compared with the ultimate limit state theory and analytical solution for verification. Departing from a good agreement from the verification, a non-linear relationship was established between the average shear strength of improved ground underneath the footing and the strength of the surrounding soil, cua/cus and bearing capacity factor, Nc. In general, it was found that the column failed in both shearing and bending modes. Â© 2018 ICE Publishing. All rights reserved.